EMPLOYEE PERFORMANCE ANALYSIS USING ROUGHT SET METHOD - Rio Andhika Putra (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
Employees are one of the values ​​of human resources in the Company that must be maintained for the development of the company. Employee performance in the Company has an important role in achieving the goals of the company. Employees must be experts in their fields and employees must also be able to work optimally. A good person's performance can be influenced by Speed ​​in Completing Work, Quality of Work, Teamwork and Service. This research was conducted using the Rought set method which aims to analyze the performance of employees at CV. Vando Jaya Group. The research method used is the rought set with a sample of 10 employees selected based on performance. The data collection techniques used were interviews, observation, questionnaires. Based on the research results show thatBased on the number of 10 samples of CV.Vando Jaya Group employees who have been tested using the Rought set application, it can be seen that the results are that the performance appraisal of 10 employees of CV. Vando Jaya Group shows the results of 2 employees are good and there are 8 employees who have excellent performance. with the number of appearances of the employee name attribute 10 (ten) times, the KMP value attribute 4 (four) times, the KP value attribute 5 times, the KT value attribute 9 times and P did not appear in the test results. So it can be seen that the most influential attribute in decision achievement is the KT attribute (TEAM Cooperation) because it has the highest number of appearances